PENANGANAN KASUS PELANGGARAN HAM TERHADAP PEKERJA MIGRAN INDONESIA OLEH LEMBAGA SOLIDARITAS PEREMPUAN - Hermawati, Istiana (Sosio Informa, 2005)
(Social Service by Woman Solidarity Institute for Migrant Workers Who are the Victims of Human Rights Violence) - This research is intended to understand the condition of Indonesian migrant workers who became the victims of Human Right Violence, and case work process carried out by Woman Solidarity Institute (WSI). The qualita tive as well as quantitative approach that applied in this research is for obtaining a comprehensive data. The primary data was collected from migrant workers and their families. There are two kind of techniques on data collection used in this research, i.e. in dept interview, participant 0bservation and documentation study. Based on this research in the year2002 there were 142 migrwt workers who became the victims of Human Right Violence. They became clients of WSI, consisting of 85,21 % of women and 14,79% men. There are two methods of case work peocess was in the form of both personal and group consultation, whereas indirect on the WSI played a roles as media between those who have problems and related parties such as PJTKI/ APJATI, Department of Men Power and Transmigration, Department of Foreign Affairs, Agency, as well as employer. There were only 33,49% cases has been successfull (claim granted). Indequate performance of WSI in carriying out those case works was among other thing caused by: less of Lawyer that rselting limited case solvings, different law system applied in Indonesia and those of foreign countries where migrant workers domicile, and there were no protection laws of foreign worker as ell. It was recommended to the Indonesian government and other relevant institution to arrange a law of social ptotection for migrant workers and provide regulation and bilateral agreement between Indonesia and destinated countries.